Knowledge of Oral Cancer and Screening Practices of Primary Care Providers at Federally Qualified Health Centers - Woosung Sohn, DDS, PhD, DrPH ; Amid 1. Ismail, BDS, MPH, DrPH; Justine L. Kolker, DDS, MS,Phd (Blackwell Synergy, 2005)
Primary care providers (PCPs) who worked in Federally-Qualified Health Centers (FQHC) in Michigan were surveyed to assess their knowledge level and practices related to screening and preventing oral cancer.